Entrepreneurial characteristics amongst co-operatives in Malaysia – preliminary evidence - Ghazali Ahmad; Mohd Rafi Yaacob; Mohamed Dahlan Ibrahim (2012)
The role of co-operative is increasingly important as such an organization provides both financial and social benefits to members and the public at large. In Malaysia, despite the increasing number of co-operatives over the years, their cumulative contribution to the country’s GNP is only less than one per cent. Such figure is far below the contribution of co-operatives in developed countries. In order to contribute significantly to the country economy, co-operative should behave entrepreneurially. Pertaining to this issue, the aim of this paper is to discuss the findings of a pilot study of entrepreneurial characteristics amongst co-operatives in Malaysia. The results were based from two separate pilot studies in which involved a number of co-operatives in the Klang Valley. Overall, the involved co-operatives show low entrepreneurial characteristics. The findings would provide valuable insights into the contribution of the co-operative sector to the national economy.